(untitled) (Teología, 2020)
In this article, Monsignor Osvaldo Santagada introduces the topic of priestly ministry and the question about its meaning in changing times. From his experience of 49 years of ministry, the author presents his contributions towards a theological renewal of priestly life. The wealth of sources that the author evokes and his own experience lead the reader through the topics of faith, prayer, love and the place of the Christian community in the life of a priest.